The maintenance of Body Fluid Homestasis during exercise when drinking ad Libitum - Tam, Nicholas (MRC/UCT RU for Exercise and Sport Medicine, 2014)
The prescription of an optimal fluid intake during exercise has been a controversial subject in sports science over the past decade. Only recently has it evolved from 'blanket' prescriptions to more individualised recommendations. Currently the American College of Sports Medicine (ACSM) advise that sufficient fluid should be drunk in order to ensure that body mass (BM) loss does not exceed >2% of starting BM in order to avoid exercise-associated medical complications. Historically BM changes have been used as a surrogate for fluid loss during exercise. It would be helpful to accurately determine fluid shifts in the body in order to provide physiologically appropriate fluid intake advice. The measurement of total body water (TBW) via deuterium oxide has been found to be the most accurate measure to detect changes in body fluid content. Thus the aim of this thesis was to understand body fluid homeostasis during exercise when drinking according to the dictates of thirst (ad libitum). This thesis begins with a review of the literature examining the basis for fluid intake prescription with the use of BM, the concepts of 'voluntary and involuntary dehydration' and the major routes by which the body is potentially able to gain and lose fluid during exercise. We initially found that changes in TBW are more variable than BM at rest, although technical machine error accounted for a majority of the total error in the TBW measurement. Interestingly BM remains very stable at rest compared to the dynamic nature of changes in TBW both daily and weekly. We also found that measurements of both BM and TBW produce reproducible results at rest. Our first finding was that with the adoption of an ad libitum fluid intake during exercise athletes participating in the study were able to finish races of varying distances without any medical complication along with a >2% BM loss. Which leads onto our second and more important finding that we have also demonstrated that despite a >2% BM loss, all of our subjects finished their respective races whilst maintaining plasma sodium concentration ([Na+]) and plasma osmolality (POsm) within the normal range when drinking ad libitum. This finding demonstrates the reality of drinking in athletes competing in various types of foot races and that it is unnecessary to drink to maintain BM in order to successfully complete races of any distance Thirdly and most pertinent finding was that associated with this >2% BM loss we measured TBW changes during these races and found that changes in BM do not track changes in TBW during real-life competition in athletes when drinking ad libitum. This finding illustrates that to some extent, sweat losses during exercise are offset by internal water sources associated with metabolic water formation and water associated with glycogen storage ensuring the maintenance of body fluid homeostasis. It was also noted that athletes performing the best often experience the greatest BM loss during the 21.1km and we found a similar trend in the 56km race. We have suggested that this can be explained by both behavioural and physiological reasons. Lastly all athletes successfully completed their respective races without encountering any exercise-associated medical complications with the adoption of an ad libitum fluid intake approach. The outcomes from this thesis support the prescription of more physiologically appropriate advice for fluid intake prescription during exercise. We hope that these studies will provide adequate corroboration that during exercise together with an ad libitum approach, athletes are able to maintain adequate hydration (maintenance of POsm and plasma [Na+]) regardless of significant decreases in BM, which is often associated with superior performance in some athletes.